Analisis Kepatuhan Akuntan Manajemen dalam Menerapkan Standar Akuntansi Pajak Penghasilan (PSAK No. 46) - Anshori, Muslich; Hariyanto, Program (Jurnal Widya Manajemen & Akuntansi, 2005)
Management accountant is profession of accountancy in the company. That is why he or she tied up to profession ethics and must obedient in apply the relevant accounting standard, including the statement of income tax accounting standard (Pernyataan Standar Akuntansi Pajak Penghasilan, PSAK No. 46), in order the financial report which are prepared get the high degree of opinion from independent auditor.